The politics of women’s subjectivity in the discourse of Indonesia’s Kabhantapi costume transformation - Lusianai, Wa Ode; Putra, Heddy Shri Ahimsa; Wahyono, Sugeng Bayu; Handayani, Rivi (Center for Sociological Studies and Community Developmen, 2025)
This study aims to problematize the position of women as subjects in the discourse of kabhantapi, the traditional costume of the Muna ethnic group in Southeast Sulawesi, Indonesia. Drawing on Laclau and Mouffe's discourse analysis, the study unpacks the hegemonic processes through which dominant groups have shaped women’s subjectivities in the contestation surrounding kabhantapi. The findings reveal that women are positioned as consumptive subjects, shaped by the intersection of democratized clothing practices-framed as ‘freedom’-and market logics conditioned by fashion capitalism. Thus, the political subject born from dislocation cannot be reduced merely to an emancipatory subject as envisioned by Laclau and Mouffe, particularly in the context of fashion. This article argues that the lack not only creates space for political subjectivation but also operates as an arena of capitalist co-optation, underscoring the need to situate women’s subjectivity within the framework of the political economy of discourse.